EFFECT OF POTASSIUM RATES ON HYDROPONICALLY-GROWN PEPPERMINT (MENTHA X PIPERITA) - El-Masry, M. H.; Morales, M. R.; Charles, D. J.; Simon, J. E. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Hydroponically grown peppermint (Mentha x piperita L) was subject to six rates (25, 150, 217, 300, 450 and 600 g/l) of potassium sulfate (K2SO4) to examine the effect on biomass, dry matter and mineral accumulation in plant organs and on leaf total essential oil yield and composition. Potassium level of 300g/l resulted in maximum biomass, dry matter accumulation and total essential oil yield. Essential oil yield was highly correlated with leaf weight, but not with leaf area. Menthone and menthol comprised 72-75 % of the total oil composition consistently across the potassium rates, even when the total oil yields were significantly affected by the potassium rates. Increasing the potassium rate had a significant effect on menthone and menthol concentrations: as the potassium rate increased from 150 to 450 g/l, the percentage of menthone increased (as relative % of total oil), while that of menthol decreased. Other essential oil constituents were significantly affected by the potassium rates by potassium rates but their percentages as part of the total oil were minor. Total nitrogen % and P content (mg/g dried leaves) decreased with each increase in K rate. K content of dried leaves increased with each increase in K increment up to 600 g/l. Ca and Mg content were also decreased with K rate increase, while no changes in Mn, Fe, B, Cu, Zn, Al and Na were observed